Comparison of Morbidity and Survival Between Primary and Interval Cytoreductive Surgery in Patients After Modified Posterior Pelvic Exenteration for Advanced Ovarian Cancer. Issue 8 (1st October 2012) - Revaux, Aurélie; Rouzier, Roman; Ballester, Marcos; Selle, Frédéric; Daraï, Emile; Chéreau, Elisabeth
Abstract : Objective: Surgical management of advanced ovarian cancer often requires low modified posterior pelvic exenteration (MPE) to achieved complete resection. The aim of this study was to evaluate the morbidity of MPE at the time of primary cytoreductive surgery (PCS) and interval cytoreductive surgery (ICS) after neoadjuvant chemotherapy. Materials and Methods: From 2001 to 2009, 63 patients underwent MPE for advanced ovarian cancer. We analyzed and compared surgical characteristics and postoperative courses between PCS and ICS. Results: Modified posterior pelvic exenteration was performed during PCS for 50 patients (79%) and during ICS for 13 patients (21%). Complete cytoreduction was achieved in 80% of patients (84% in the PCS group and 69% in the ICS group; ns). There was no significant difference between the PCS and ICS groups in the type and the rate of standards or radical surgical procedures. Patients with ICS had a shorter length of stay in the intensive care unit (0.9 vs 2.7 days; P = 0.009), but there was no difference in the total length of hospitalization ( P = 0.94). The global rate of postoperative complications was 76%. No differences were found between the 2 groups in digestive or extradigestive complications, iterative surgery, or interventional radiology procedures. The median overall survival was 49.4 months in the PCS group and 27.1 months in the ICS group ( P = 0.27), and the median progression-free survival time in both groups was 20 months. Conclusions: There was no difference in the occurrence of postoperative complications between PCS and ICS, especially in morbidity related to MPE. The specific morbidity of this surgical procedure remained low compared with the overall morbidity in cases of extensive surgery.